2010
DOI: 10.1007/s11434-009-0695-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of cloud point extraction for removal of nanosized copper oxide from wastewater

Abstract: Triton X-114 based cloud point extraction has been demonstrated to be an advantageous approach for the recovery of nanosized copper oxide (NCO) from water. The removal of NCO was influenced by the concentrations of TX-114 and salt, incubation temperature and time, as well as solution pH. With the addition of 0.3% (w/v) Triton X-114, over 88% of the spiked NCO was removed from wastewater after incubation at 35°C for 2 h and centrifugation, whereas over 85% of NCO was recovered after incubation at 28°C for 20 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…It is indicated that the cationic surfactant is the most suitable to serve as the collector of CuO nanoparticles at pH 6.5. Liu et al (2010) observed that the zeta potential of CuO nanoparticles was zero at pH 6.0 and decreased to a negative value as pH increased over this point. At pH 6.5, the surface of CuO nanoparticles was negatively charged, so CTAB was able to more effectively capture CuO nanoparticles onto the gasliquid interface than the other two surfactants according to the charge theory.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…It is indicated that the cationic surfactant is the most suitable to serve as the collector of CuO nanoparticles at pH 6.5. Liu et al (2010) observed that the zeta potential of CuO nanoparticles was zero at pH 6.0 and decreased to a negative value as pH increased over this point. At pH 6.5, the surface of CuO nanoparticles was negatively charged, so CTAB was able to more effectively capture CuO nanoparticles onto the gasliquid interface than the other two surfactants according to the charge theory.…”
Section: Resultsmentioning
confidence: 94%
“…The removal or recovery of nanoparticles from water faces two major challenges: one is that they cannot freely precipitate due to their high dispersity in water and the other is that their concentrations in water are extremely low (Westerhoff et al 2011;Liu et al 2010). Thus, centrifugation and membrane separations are not suitable options due to their high separation costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparably, CPE procedures were established for CuO NPs and ZnO with enrichment factors of 100 and 220 and extraction efficiencies of almost 90 and 64–123 %, respectively [ 11 , 12 ]. In the case of ZnO NPs, TEM and UV/Vis measurements revealed that particle size and shape were stable over 2 months of storage.…”
Section: Cpe and Fractionationmentioning
confidence: 99%
“…Amoxicillin can be applied as a ligand to the determine copper(II) by CPE joined with spectrofluorometric in the presence of Triton X-114 as the surfactant [25]. Applied to extract Cu, Co and Ni in water testers using 2-(5-bromo-2-pyridylazo)-5-(diethyl amino) phenol (5-Br-PADAP) as ligand and Triton X-114 [26]. The study indicates that the CPE has excellent potential in Nano-materials removal from wastewater Triton X-114 suitable for the recovery of Nano sized Copper oxide (NCO) from the water.…”
Section: Introductionmentioning
confidence: 99%